Pengaruh Tingkat Pendidikan terhadap Komunikasi Informasi Penempatan Tenaga Kerja di Kabupaten Langkat dalam Perspektif Ekonomi Syariah - Nadia Eka Putri; Agus Purwanto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study is motivated by the importance of education level in enhancing individuals’ ability to understand and utilize labor placement information communication, particularly within the context of financing beneficiaries. The study aims to analyze the effect of education level on labor placement information communication in Langkat. This research employs a quantitative approach with an associative research design. The population of the study consists of 70 respondents, all of whom were included as research samples using the total sampling technique. Data were collected through closed-ended questionnaires, while data analysis was conducted using simple linear regression. The results indicate that education level has a positive and significant effect on labor placement information communication. The coefficient of determination (R Square) value of 0.541 shows that education level contributes 54.1% to labor placement information communication, while the remaining 45.9% is influenced by other factors outside this study. The t-test results show a significance value below 0.05, indicating that the research hypothesis is accepted. In conclusion, education level plays a strategic role in improving the effectiveness of labor placement information communication, particularly in assisting job seekers in understanding procedures, requirements, and available job opportunities. Therefore, improving the quality of and access to education is an important aspect in supporting more equitable and sustainable labor placement policies.